Tipologi Pemikiran Muamalah Mu'āṣirah Dr. Muhammad Utsman Syabir dalam Kitab al- Muamalah al-Maliyah al- Mu'āṣirah fi al-Fiqh al-Islamy - asad aham; Ibno Hajar (Afaquna: Jurnal Cakrawala Islam, 2026)
The development of contemporary economics requires muamalah fiqh to continuously perform ijtihad in formulating rulings on new issues such as copyright, insurance, paper currency, credit cards, shares, and bonds. One scholar who systematically responded to these issues is Dr. Muhammad Uthman Syabir through his book al-Muamalah al-Maliyah al-Mu’āṣirah fi al-Fiqh al-Islamy. Previous studies generally discuss multi-contract issues, maqāṣid al-sharī'ah, and ijtihad instruments such as istihsan, istishāb, ‘urf, and maslaḥah mursalah partially at the level of sharia financial products, without mapping a scholar’s methodological position within the typology of Islamic legal thought (traditionalist, liberalist, moderate), leaving a gap in fully understanding the standing of Syabir’s thought. This study aims to answer how Syabir’s intellectual background, ijtihad method, and typology of contemporary muamalah thought can be characterized. The study employs a qualitative method with a library research approach; primary data consist of al-Muamalah al-Maliyah al-Mu’āṣirah fi al-Fiqh al-Islamy, while secondary data comprise supporting journal articles and books. Data were analyzed using the Miles and Huberman interactive model through reduction, display, and conclusion drawing/verification. The findings show that Syabir’s ijtihad methodology is moderate in giving balanced weight to naql and ‘aql, yet in practice his istidlāl leans closer to the ahl al-ra’yi character due to his dominant use of maslaḥah mursalah, istishlah, istishāb, and ‘urf. This study recommends further research on Syabir’s other works to obtain a more comprehensive map of his thought.